Pengaruh Financial Distress, Komite Audit dan Pergantian Auditor Terhadap Ketepatan Waktu Pelaporan Keuangan - Nurhaniza; Tiya Nurfauziah; Sari Rusmita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The purpose of this study is to investigate and evaluate the effects of audit committees, financial crisis, and auditor turnover on the promptness of financial reporting. This study's focus is on energy-related companies that mine and are listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023—a total of 19 issuers. This study makes use of secondary data, with 57 samples chosen as a result of purposive sampling techniques. The selection of the sample is predicated on particular attributes. Using SPSS version 29 as the analytic tool, the analysis is carried out by applying logistic regression and descriptive statistical methods. Regression coefficient values of 0,062 show that there is no relationship between financial difficulties and the timely submission of financial statements and level of significance of 0,575 > 0,05. As a result, there is a slight but positive correlation between the financial distress variable and the promptness of financial reporting. With a regression value of -3,886 and a significance value of 0,002, which is less than 0,05, the audit committee does not infer the timeliness of financial reporting. When taken into partial consideration, it is noted that the audit committee might have a negative and considerable impact on the timely submission of financial reports. With a regression value of 1,637 and a significance of 0,169 > 0,05, it is clear that, when taken into partial consideration, the change in the auditor may have a positive but non-significant impact on the timeliness of financial reporting. However, the change in the auditor does not appear to have any effect on the timeliness of financial reporting.